Sensitivitas Antara Antibiotik Meropenem dan Seftazidin Terhadap Pseudomonas aeruginosa Strain ATCC 15442 Pada Pasien Pneumonia di RSUP dr. Cipto Mangunkusumo Jakarta Pusat - Diah Lestari; Husyain Djajaningrat; Febri Wulan Dari; Dean Handimulya (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Pneumonia is an acute lower respiratory tract infection in the lung parenchyma that has a high level of treatment resistance and is a nosocomial bacterial transmission. One of the nosocomial bacteria in hospitals is Pseudomonas aeruginosa, which is a Multi Drug Resistant (MDR) bacteria, a pathogen that causes infections that are resistant to at least three antimicrobial agents. The antimicrobials included are meropenem and ceftazidime, these two antibiotics are the best choice of last-line drugs in the treatment of MDR bacteria. Effective prevention and treatment of bacterial colonization and infection in pneumonia patients needs to be done to reduce the negative impact of antibiotic use. The aim of this study was to determine the sensitivity between the antibiotics meropenem and ceftazidime against Pseudomonas aeruginosa bacteria in pneumonia patients at RSUPN dr. Cipto Mangunkusumo, Central Jakarta. The research method was analytical observational using a cross sectional design with medical record data sources on 105 pneumonia patients who underwent sputum culture examination. Data analysis using the Mann-Whitney Test at 95% CI (α = 0.05). The research results showed that the majority of patients were male, 69 people with an elderly age category of 51 people (48.6%). The results of the antibiotic sensitivity of meropenem were 76.25% and ceftazidime were 69.5%, with a p-value of 0.000. The average sensitivity of the antibiotic meropenem is 20.59, more sensitive than the antibiotic ceftazidime, an average of 20.50 with a difference in sensitivity of 9%. The conclusion is that there is a difference in the sensitivity of the antibiotics meropenem and ceftazidime against Pseudomonas aeruginosa bacteria in pneumonia patients at RSUPN Dr. Cipto Mangunkusumo, Central Jakarta, the antibiotic meropenem is more sensitive than the antibiotic ceftazidime.  Keywords: Meropenem, Pneumonia, Pseudomonas aeruginosa,  Seftazidim.